Determinasi Faktor Pendukung dan Penghambat Transformasi Digital di Lembaga Pendidikan - Pupu Fauziah; Hielda Amini (JMPI: Jurnal Manajemen Pendidikan Islam, 2025)
This study analyzes the supporting and inhibiting factors of digital transformation in educational institutions, as well as the strategies for its implementation. The research employs a qualitative method with a literature review approach. The findings indicate that supporting factors include infrastructure readiness, human resource competencies, adaptive organizational culture, management support, content quality, data security, student engagement, and continuous evaluation. In contrast, inhibiting factors include resistance to change, budget limitations, low digital literacy, rigid procedures, and minimal user involvement. Recommended strategies encompass human resource training, infrastructure improvement, fostering an innovative culture, pro-digital policies, development of interactive content, risk management, and active student participation. Integrating these aspects is expected to enhance efficiency, quality of educational services, and the sustainability of digital transformation.